2019
DOI: 10.3390/diagnostics9040126
|View full text |Cite
|
Sign up to set email alerts
|

Association Between VEGF Expression and Diffusion Weighted Imaging in Several Tumors—A Systematic Review and Meta-Analysis

Abstract: To date, only a few studies have investigated relationships between Diffusion-weighted imaging (DWI) and Vascular endothelial growth factor (VEGF) expression in tumors. The reported results are contradictory. The aim of the present analysis was to review the published results and to perform a meta-analysis regarding associations between apparent diffusion coefficients (ADC) derived from DWI and VEGF expression. MEDLINE library was screened for relationships between ADC and VEGF expression up to January 2019. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Therefore, the selection of cases with active tumor angiogenesis through imaging or histological evaluation may be conducive to improving the ORR. Some researchers have confirmed that the DWI phase of MRI is effective in evaluating tumor angiogenesis (125). Wu Xin et al analyzed 88 cases of eCCA and found that ADC values were negatively correlated with MVD and VEGF (p < 0.05), indicating that DWI could be performed for the selection of BTC patients who may benefit from antiangiogenic treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the selection of cases with active tumor angiogenesis through imaging or histological evaluation may be conducive to improving the ORR. Some researchers have confirmed that the DWI phase of MRI is effective in evaluating tumor angiogenesis (125). Wu Xin et al analyzed 88 cases of eCCA and found that ADC values were negatively correlated with MVD and VEGF (p < 0.05), indicating that DWI could be performed for the selection of BTC patients who may benefit from antiangiogenic treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond sole cellularity, ADC values are associated with important histopathology parameters, re ecting proliferation potential (Ki 67) and tumor suppressor genes p53 [49,50]. However, some immunohistochemical features of angiogenesis were not associated with ADC values [51]. In short, there is ongoing debate which features of tumors can be predicted by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liposomes give the opportunity to deliver both hydrophobic and hydrophilic compounds, but also genetic material. In MPM treatment, liposomes are exploited to deliver chemotherapeutics, such as doxorubicin [54,55], or pemetrexed [56,57], with the main goal to increase the concentration of drugs in the peritoneal cavity, to avoid fast degradation of drug molecules, and to have the possibility Comparing the two images, it can be observed that even if the CT/PET scan allows a greater morphological detail, the IVIM sequence has an equal capacity to highlight, with hyper-intensity of the signal, the same functional aspects.…”
Section: Nanoparticles (Nps) As Novel Promise For Mpmmentioning
confidence: 99%
“…Moreover, liposomes give the opportunity to deliver both hydrophobic and hydrophilic compounds, but also genetic material. In MPM treatment, liposomes are exploited to deliver chemotherapeutics, such as doxorubicin [54,55], or pemetrexed [56,57], with the main goal to increase the concentration of drugs in the peritoneal cavity, to avoid fast degradation of drug molecules, and to have the possibility to prolong the release of the drug. For example, Ando et al demonstrated that an injection into the pleural cavity of pemetrexed loaded into liposomes had more suppressive effect on tumor growth in an orthotopic mesothelioma mouse model, compared to free pemetrexed.…”
Section: Nanoparticles (Nps) As Novel Promise For Mpmmentioning
confidence: 99%